Cytosolic UDP-Gal biosynthetic machinery is required for dimerization of SLC35A2 in the Golgi membrane and its interaction with B4GalT1 - Wiertelak, Wojciech; Pavlovskyi, Artem; Olczak, Mariusz; Maszczak-Seneczko, Dorota (Frontiers in Molecular Biosciences, 2025)
Glycosylation is a vital post-translational modification involving the addition of sugars to proteins and lipids, facilitated by glycosyltransferases and dependent on nucleotide sugar donors like UDP-galactose (UDP-Gal). This study examines how disruptions in UDP-Gal synthesis affect protein-protein interactions critical for glycosylation. Using CRISPR/Cas9, we generated HEK293T cell lines lacking key enzymes of the Leloir pathway: UDP-galactose 4′-epimerase (GALE), galactose-1-phosphate uridylyltransferase (GALT), or both. The knockout of GALE led to a significant reduction in intracellular UDP-Gal levels and altered N-glycan profiles, indicating impaired galactosylation. Through the NanoBiT assay, we observed that knocking out GALE alone or both GALE and GALT diminished the ability of the UDP-Gal transporter SLC35A2 to form homomers and to interact with the beta-1,4-galactosyltransferase 1 (B4GALT1). These findings suggest that the nucleotide sugar availability and/or the presence of the corresponding enzymes in the cytoplasm influences the formation of protein complexes involved in glycosylation in the Golgi apparatus, potentially affecting the glycosylation process itself. Our study highlights the dynamic nature of the glycosylation machinery and suggests that the interactions between glycosylation proteins are responsive to changes in nucleotide sugar levels. This opens new avenues for understanding the mechanisms underlying glycosylation and for investigating congenital glycosylation disorders.